Low‐carbon coordinated scheduling of integrated electricity‐gas distribution system with hybrid AC/DC network - Yuliang Qing; Tianqi Liu; Chuan He; Lu Nan; Guicen Dong; Weikai Gao; Yinqian Yu (IET Renewable Power Generation, 2022)
Abstract Under the promotion of low‐carbon policies, the coordinated operation of integrated electricity‐gas distribution system (IEGDS) considering CO2 emission is of great significance to accelerate the process of energy conservation and could improve the economy of IEGDS. The paper proposes a low‐carbon coordinated operation of the IEGDS considering hybrid AC/DC distribution network, carbon capture and carbon storage. Firstly, the coordinated scheduling model of the IEGDS is discussed, with coupling constraints of gas turbines and power‐to‐gas. Secondly, the paper presents the model of hybrid AC/DC power distribution system, where non‐linear network constraints are relaxed into second‐order‐cone programming forms. Regarding carbon emission, the CO2 produced by fossil fuel burning can be partly captured by carbon capture plant, stored in carbon storage tank, and transported by trucks to carbon storage warehouse that trades with the carbon market. With the cooperation of various components, a comprehensive model considering carbon flow and trading in the distribution system is innovatively presented here. Numerical experiments validate the effectiveness of proposed low‐carbon coordinated scheduling model for the integrated electricity and natural gas distribution system.